Anatomical variations of the anterior belly of the digastric muscle in Thai cadavers: A cross-sectional study - Arayapisit T. (2023)
Aim: Because the digastric muscle is considered as an anatomical landmark, its variations may emphasize clinicians to be cautious during surgery. However, previous studies from different ethnicities reported a wide range of occurrence and several types of this muscle variation, pointing the necessity of the data from local population to better treatment decisions. Thus, this study aimed to explore the variations of the anterior belly of the digastric muscle in Thai cadavers. Materials and Methods: This cross-sectional study investigated the submental region of 91 cadavers by convenient sampling method. The characteristics of the variation in the anterior belly were recorded in accordance with sex and side of the cadavers. Multiple logistic regression was calculated for determining the association of occurrence of muscle variation with sexes and sides (α = 0.05). Results: Among 91 cadavers, the accessory bundles were observed in 16 cadavers (10 males and 6 females). The presence of the additional belly was sex and side independent. Three variation types were observed; the arrowhead type and the double-headed type have been previously reported, whereas the asymmetrical fan-shaped type is the new variant that has never been described before. Conclusions: The variation of the anterior belly of the digastric muscle including the new variant can be seen in Thais with low occurrence. To our knowledge, the present study is the first report of the aberrations of the digastric muscle in the Southeast Asian population. Therefore, our study provides the basis for anatomical study of muscular variants and helps surgeons plan the operation to prevent iatrogenic injuries.